Integrating Culture and Technology in Smart Tourism: A Case Study of Solo - Pratita Rara Raina; Roudlotul Jannati Rochnadia Noorva Yudhitya; Priaji Iman Prakoso (Politeknik Siber Cerdika Internasional, 2026)
Background: The development of smart tourism requires an integrated ecosystem framework that connects technology, governance, business, and visitor experience. Objective: This study aims to develop a comprehensive Smart Tourism Ecosystem (STE) framework and examine its relevance to Solo City, Indonesia. Methods: This study employed a qualitative, literature-based research design that combining a Systematic Literature Review (SLR) and a narrative review to established a comprehensive theoretical foundation while gaining deep contextual insight. Results: The study identifies five key dimensions of the STE: Smart Technology, Smart Business Ecosystem, Smart Governance, Tourist Experience, and Smart Destination. The findings indicate that Solo has strong potential to develop as a culturally driven smart destination, supported by its creative economy, digital initiatives, and collaborative stakeholders. Conclusion: While the proposed framework offers strategic insights, further empirical research is needed to assess local readiness and support sustainable smart tourism implementation in Indonesia.